If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3a + 3) + -3 = 5 Reorder the terms: 2(3 + 3a) + -3 = 5 (3 * 2 + 3a * 2) + -3 = 5 (6 + 6a) + -3 = 5 Reorder the terms: 6 + -3 + 6a = 5 Combine like terms: 6 + -3 = 3 3 + 6a = 5 Solving 3 + 6a = 5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6a = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 6a = 5 + -3 6a = 5 + -3 Combine like terms: 5 + -3 = 2 6a = 2 Divide each side by '6'. a = 0.3333333333 Simplifying a = 0.3333333333
| 6(4x-5)=12 | | 15(x+17)=555 | | 10-2x=8y | | 12.5*10= | | 131/4+165/6+91/3 | | 6.5+X=2.7 | | 8=3-4(x-2) | | x^2+3lnx-14=0 | | 5/8x=9/4-3/8 | | 8-9=x-5+4 | | 6b-4b=6 | | x^2+2=2+3x | | x^2+1=25+x^2 | | 3x/-8-4x=-1 | | 0=-500x^2+10000x+100000 | | 17-3=x+5-3 | | 14-3=x+5-3 | | 18-(2x+1)=x-1 | | 3x+3=140 | | 18-(2x-1)=x-1 | | 1-x=4-2x | | 22+p=-12 | | 3x+3y=140 | | 5x+25=10x+17 | | 4n-6=34 | | Y=1.6(9)+3 | | .8x-2.3=1.9x+2.8 | | 2x+1=5x-5 | | 3x+9=-5n+1 | | ax+12=6bx-12 | | 3x+9=5n+1 | | .5x-2.8=3.2x+2.3 |